2017
DOI: 10.1002/jcla.22191
|View full text |Cite
|
Sign up to set email alerts
|

Associations of urinary, glomerular, and tubular markers with the development of diabetic kidney disease in type 2 diabetes patients

Abstract: Conclusion:Only the tubular markers α 1 -MG and β 2 -MG were associated with eGFR independent of albuminuria, suggesting that they may play an important role in the development of DKD. K E Y W O R D Sα1-microglobulin, β2-microglobulin, albuminuria, diabetic kidney disease, glomerular filtration rate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Urine IgG and transferrin excretion has been previously observed in normoalbuminuric patients with diabetes and has been associated with hypertension and hyperfiltration [ 24 , 25 ]. In accordance with previous studies [ 26 , 27 ], we observed increased urine IgG and transferrin in a subgroup with moderately increased albuminuria and both proteins were specific markers of kidney disease. These are notable observations, especially considering high molecular weight of IgG (150 kDa) that preserves the protein from being filtered by healthy glomeruli [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Urine IgG and transferrin excretion has been previously observed in normoalbuminuric patients with diabetes and has been associated with hypertension and hyperfiltration [ 24 , 25 ]. In accordance with previous studies [ 26 , 27 ], we observed increased urine IgG and transferrin in a subgroup with moderately increased albuminuria and both proteins were specific markers of kidney disease. These are notable observations, especially considering high molecular weight of IgG (150 kDa) that preserves the protein from being filtered by healthy glomeruli [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…19,20 In addition, the significant correlation of eGFR with urinary α1-MG/Cr in univariate analysis lost after multivariate analysis, it is different from our previous study in diabetic patients. 11 Similarly, the relatively normal kidney function and younger age may interpret this result, too.…”
Section: Discussionmentioning
confidence: 94%
“…However, there are few detailed and comprehensive studies on the reference interval of urinary α1‐MG concentrations in Chinese people, and we usually refer to the western results. But our recent studies found that, the incidence of elevated urinary α1‐MG/Cr was higher in men than in women, and male was the most important risk factor associated with tubular injury . Similarly, a study about urinary α1‐MG in Singapore also found the urinary α1‐MG excretion increased with age, and was higher in men (1.41 mg/mmol urine creatinine) than in women (1.14 mg/mmol urine creatinine) .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“… 11 β2-MG and cystatin C are reliable and important markers of renal damage in patients with diabetes, and they are significantly elevated compared with control subjects. 12 , 13 In women with PCOS, cystatin C may be a new strategy in clinical practice for early detection of individuals who are at high risk for long-term metabolic and cardiovascular events. 14 …”
Section: Introductionmentioning
confidence: 99%